The PERMA well-being scale assessment in undergraduate students: confirmatory factor analysis and network analysis - Yurayat, Phamornpun; Choomphunuch, Bovornpot; Suk-erb, Wipanee; Lebkhao, Dussadee; Jornkokgoud, Khanitin (Institute of Advanced Engineering and Science, 2025)
The mental health issues among undergraduate students have become increasingly recognized as a pressing concern, often impacting their overall well-being over time. Despite escalating scholarly attention to students’ well-being, a significant gap persists in theoretical frameworks and measurement instruments with established benchmarks, remarkably those applicable to the Thai context. This study aims to develop and validate a contextually appropriate well-being instrument for Thai university students, grounded in the PERMA model, which examines five dimensions: positive emotion, engagement, relationships, meaning, and accomplishment. A multistage sampling approach was utilized to enlist 1,080 participants for an online questionnaire incorporating the PERMA well-being scale. The data were examined through confirmatory factor analysis (CFA) and network analysis to assess the structural validity and inter-item correlations. Results from the second-order CFA yielded an excellent model fit with a root mean square error of approximation (RMSEA) of 0.013, with all the constructs significant at p<0.001. In addition, network analysis showed the centrality within constructs. The findings revealed that the PERMA model was indicative of Thai university students’ well-being exhibited robust internal consistency, and significant intra-construct correlations. This contextually relevant instrument yielded valuable insightful information for educators and policymakers in Thailand. This could thus help shape strategies to evaluate and improve student well-being.